Plasma Oxylipins: A Potential Risk Assessment Tool in Atherosclerotic Coronary Artery Disease - Le, D. Elizabeth; García-Jaramillo, Manuel; Bobe, Gerd; Alcazar Magana, Armando; Vaswani, Ashish; Minnier, Jessica; Jump, Donald B.; Rinkevich, Diana; Alkayed, Nabil J.; Maier, Claudia S.; Kaul, Sanjiv (Frontiers in Cardiovascular Medicine, 2021)
Background: While oxylipins have been linked to coronary artery disease (CAD), little is known about their diagnostic and prognostic potential. Objective: We tested whether plasma concentration of specific oxylipins may discriminate among number of diseased coronary arteries and predict median 5-year outcomes in symptomatic adults. Methods: Using a combination of high-performance liquid chromatography (HPLC) and quantitative tandem mass spectrometry, we conducted a targeted analysis of 39 oxylipins in plasma samples of 23 asymptomatic adults with low CAD risk and 74 symptomatic adults (≥70% stenosis), aged 38–87 from the Greater Portland, Oregon area. Concentrations of 22 oxylipins were above the lower limit of quantification in >98% of adults and were compared, individually and in groups based on precursors and biosynthetic pathways, in symptomatic adults to number of diseased coronary arteries [(1) n = 31; (2) n = 23; (3) n = 20], and outcomes during a median 5-year follow-up (no surgery: n = 7; coronary stent placement: n = 24; coronary artery bypass graft surgery: n = 26; death: n = 7). Results: Plasma levels of six quantified oxylipins decreased with the number of diseased arteries; a panel of five oxylipins diagnosed three diseased arteries with 100% sensitivity and 70% specificity. Concentrations of five oxylipins were lower and one oxylipin was higher with survival; a panel of two oxylipins predicted survival during follow-up with 86% sensitivity and 91% specificity. Conclusions: Quantification of plasma oxylipins may assist in CAD diagnosis and prognosis in combination with standard risk assessment tools.